The impact of the implementation of gender politics in the oil industry. Neuquen case (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
The international organisms has suggested to the public institutions and private companies the implementation of politics and programs to stop the gender discrimination in the place of work.  Neuquén is the biggest producer of oil in Argentina, from there that the most important international oil companies in the world operate in that region. This article is an approach of that query, of how many of them consider that the equality of gender  is important to be included in their objectives and internal politics.
Keywords: Female work; political gender; oil fields corporation